Attenuation of acoustic wave excited by piezoelectric aggregate in asphalt pavement and its application to monitor concealed cracks. (20th August 2019) - Ji, Xiaoping; Hou, Yueqin; Chen, Yun; Zhen, Yikang
Highlights: Coefficient of acoustic wave attenuation a decreases as crack width increases. Value of a decreases as asphalt viscosity, NMPS and voids increase. Value of a decays fast when distance is within 50 cm, subsequently becomes smooth. Value of a increases as temperature and moisture increase. AAD is independent of mixture properties and grows linearly with crack width. Abstract: The use of sensors to monitor concealed cracks in asphalt pavement has become a research topic of interest. In this paper, piezoelectric aggregates (PAs) were embedded into an asphalt pavement. One was used as an actuator for transmitting a signal, and the other as a sensor for receiving the signal. The coefficient of acoustic wave attenuation a, referring to the amplitude ratio of the excitation signal to receiving signal, decreases as crack width in an asphalt pavement increases, indicating that the application of acoustic waves excited by PA to monitor concealed cracks of asphalt pavement is feasible. The driving frequency imposes obvious influence on the a, which is at its maximum when the driving frequency is 500 Hz. The value of a decreases as asphalt viscosity, nominal maximum particle size and air voids increase, and as asphalt content decreases. Temperature and moisture have obvious influences on wave attenuation, and the value of a increases as temperature and moisture increase. A more universal indicator–average absolute deviation ( AAD ) was proposed, which is independent of the asphalt mixture properties and grows linearly with the crack width in an asphalt pavement. In practical engineering, the pavement concealed cracks can be monitored by the acoustic saves excited by PA and be calculated by ADD . This study provides a reference for the development and application of intelligent monitoring of concealed damage in asphalt pavements.